Overexpression of PD-L1 is an Independent Predictor for Recurrence in HCC Patients Who Receive Sorafenib Treatment After Surgical Resection - Tan, Yifei; Xu, Qing; Wu, Zhenru; Zhang, Wei; Li, Bo; Zhang, Bohan; Xu, Xi; Zhang, Bo; Yan, Ke; Song, Jiulin; Lv, Tao; Yang, Jian; et al. (Frontiers in Oncology, 2022)
Overexpression of PD-L1 is an independent predictor for recurrence in HCC patients who receive sorafenib treatment after surgical resection